Social Service Movement as An Effort to Help People Around Universitas Kadiri andReduce Covid-19 Movement Space - Komari Ana; Lolyka Dewi Indrasari; Afiff Yudha Tripariyanto; Heribetus Budi Santosa; Sri Rahayuningsih (ASEAN Journal of Empowering Community, 2021)
Community service as one form of implementation of tri dharma college. Social service movement to help the economy and reduce the movement space of covid-19 as a goal achieved. The intended subject is to students at Budi Mulia Orphanage and seniors in Pojok village, Mojoroto district. Preparation of activities includes schedule arrangement, location arrangement, questionnaires, and attendance of participants. On April 25, 2021, at the Orphanage "Budi Mulia" Tambakrejo, Gurah, Kediri regency on April 26, 2021, at the Sports Hall (GOR) Kadiri University. This activity stated that participants had understood enough about the material presented about the goals achieved. The value of understanding for the elderly is 3.8 and for students is 3.4. Overall the matter falls into the category of quite understandable. The next activity is the distribution of food packages and masks to participants. The division went smoothly and was well received. Community service activities organized by the IWANIK team can provide a positive response to participants and provide benefits following their functions.